Discordance Among Patients and Ophthalmologists Regarding the Burden of Intravitreal Injections - Robinson K; Cooper SJ; Persaud S; Frederick JL; Singh RP (Clinical Ophthalmology)
Katie Robinson,1 Simon J Cooper,1 Sasha Persaud,1 Jennifer L Frederick,1 Rishi P Singh2 1Office of Medical Affairs, Vindico Medical Education, Thorofare, NJ, USA; 2Martin Hospitals, Cleveland Clinic, Stuart, FL, USACorrespondence: Katie Robinson, Office of Medical Affairs Vindico Medical Education, 6900 Grove Road Building #100, Thorofare, NJ, 08086, USA, Email krobinson@vindicoCME.comPurpose: To determine how patients with neovascular age-related macular degeneration (nAMD) or diabetic macular edema (DME) perceive their disease and its treatment and to assess the degree of alignment between patient and clinician perceptions.Patients and Methods: In June 2024 a survey of 101 patients (50 with DME and 51 with nAMD) and 100 ophthalmologists who treat these conditions completed surveys.Results: Sixty-six percent and 86% of patients with DME and nAMD, respectively, reported receiving intravitreal injections at least once every 8 weeks. Eighty-two percent required a caregiver and/or public transportation to get to their appointments. The most significant symptoms for patients with DME were vision loss over time (2.89 out of 4.0) and blurred or double vision (2.76), and for those with nAMD were poor night vision (3.43), seeing in low-light conditions (3.27), and blurred vision (2.96). The proportion of patients who were dissatisfied with the education and counseling they received about their disease was greater for nAMD (31%) compared with DME (11%; P < 0.01). Ophthalmologists overestimated the extent to which patients perceived that injections were necessary (mean Likert scale score 3.41 vs 3.00; P < 0.01) and that patients experienced insurance barriers to receiving treatment (3.00 vs 2.46; P < 0.01). They overestimated the extent to which patients became less nervous with subsequent injections after the first (3.40 vs 2.94; P < 0.01) and underestimated their difficulty of getting to appointments (2.30 vs 2.64; P < 0.01).Conclusion: This study highlights the significant burden experienced by patients undergoing intravitreal injections and identifies key areas of discordance between patient and clinician perceptions. Targeted education and counseling focused on these differences is indicated to improve patient satisfaction and outcomes.Keywords: nAMD, DME, anti-VEGF, patient experience, retina